2017
DOI: 10.1186/s13045-017-0447-6
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the novel BCR kinase inhibitor IQS019 in preclinical models of B-cell non-Hodgkin lymphoma

Abstract: BackgroundPharmacological inhibition of B cell receptor (BCR) signaling has recently emerged as an effective approach in a wide range of B lymphoid neoplasms. However, despite promising clinical activity of the first Bruton’s kinase (Btk) and spleen tyrosine kinase (Syk) inhibitors, a small fraction of patients tend to develop progressive disease after initial response to these agents.MethodsWe evaluated the antitumor activity of IQS019, a new BCR kinase inhibitor with increased affinity for Btk, Syk, and Lck/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“… 45 , 46 It has been reported that the small-molecule inhibitor to Lyn is a novel target for DLBCL patients. 47 , 48 Our results showed DCZ3301 inhibited Lyn activation along with decreased STAT3 activation. More importantly, the protein expressing of phospho-STAT3 in Lyn-OE cells suggests that DCZ3301 induces STAT3 phosphorylation by inhibiting Lyn activation directly in DLBCL.…”
Section: Discussionmentioning
confidence: 54%
“… 45 , 46 It has been reported that the small-molecule inhibitor to Lyn is a novel target for DLBCL patients. 47 , 48 Our results showed DCZ3301 inhibited Lyn activation along with decreased STAT3 activation. More importantly, the protein expressing of phospho-STAT3 in Lyn-OE cells suggests that DCZ3301 induces STAT3 phosphorylation by inhibiting Lyn activation directly in DLBCL.…”
Section: Discussionmentioning
confidence: 54%
“…For functional studies, primary tumor cells from five patients were isolated, cryopreserved, and conserved within the hematopathology collection of our institution (Hospital Clínic-IDIBAPS Biobank R121001-094), as previously described. 28 Primary cultures were maintained in complete medium in the presence of the mesenchymal cell line StromaNKTert (Riken BioResource Center) 29 at a 4:1 ratio, to prevent spontaneous ex vivo apoptosis. The ethical approvals for this project, including informed consent from the patients, were granted following the guidelines of the Hospital Clínic Ethics Committee (Institutional Review Board, registration number 2012/7498).…”
Section: Methodsmentioning
confidence: 99%
“…Whole cell proteins were extracted from 10 7 DLBCL cells as previously described. 28 Proteins (30-50 μg/lane) were subjected to 10–12% sodium dodecylsulfate-polyacrylamide gel electrophoresis, and transferred onto polyvinylidene difluoride membranes (Immobilon-P; Millipore), or nitrocellulose membranes (Amersham Biosciences). Membranes were then incubated with primary and secondary antibodies ( Online Supplementary Materials and Methods ) and visualized on a mini-LAS4000 device (Fujifilm) by enhanced chemiluminescence (ECL, Amersham Life Science).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations